Predictive value of amplitude integrated electroencephalography combined with heart rate variability parameters in early prognosis of acute ischemic stroke patients after mechanical thrombectomy. - WANG, Ju; ZHANG, Ming; HAN, Bing-sha; LI, Jiao; LI, Yan-ru; FENG, Guang (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To explore predictive efficiency of amplitude integrated electroencephalography (aEEG) combined with heart rate variability (HRV) parameters in early prognosis of acute ischemic stroke patients after mechanical thrombectomy. Methods A total of 137 patients with acute ischemic stroke undergoing mechanical thrombectomy in He'nan Provincial People's Hospital were enrolled as the research objects between April 2021 and August 2024. According to 90 d prognosis by modified Rankin Scale (mRS), they were divided into good prognosis group (mRS score ≤ 2, n = 77) and poor prognosis group (mRS score > 2, n = 60). The clinical data (sociodemographic data, laboratory examination data at admission) were collected, preoperative aEEG data were collected to obtain aEEG score. After admission dynamic ECG examination was performed to obtain HRV parameters [standard deviation of normal R-R intervals (SDNN), standard deviation of normal R-R intervals index (SDNN index), root mean square successive difference of normal R-R intervals (RMSSD), and percentage of normal-to-normal intervals differing by more than 50 ms (pNN50)]. The influencing factors of early prognosis in acute ischemic stroke patients after mechanical thrombectomy were screened by univariate and multivariate Logistic regression analyses, and predictive efficiency of aEEG score and HRV parameters of early prognosis in acute ischemic stroke patients after mechanical thrombectomy was evaluated by area under the curve (AUC) of receiver operating characteristic (ROC) curve. Results Multivariate Logistic regression analysis showed that higher National Institutes of Health Stroke Scale (NIHSS) score (OR = 1.779, 95%CI: 1.038-3.050; P = 0.037), higher neutrophil-to-lymphocyte ratio (OR = 1.718, 95%CI: 1.016-2.905; P = 0.044), and higher aEEG score (OR = 1.933, 95%CI: 1.071-3.487; P = 0.029) were risk factors for early poor prognosis in acute ischemic stroke patients after mechanial thrombectomy, while higher SDNN (OR = 0.908, 95%CI: 0.864-0.953; P = 0.000) and higher pNN50 (OR = 0.930, 95%CI: 0.866-0.998; P = 0.043) were protective factors for good prognosis. The AUC values of aEEG score, SDNN, SDNN index, RMSSD and pNN50 for predicting early poor prognosis were 0.673, 0.685, 0.685, 0.734 and 0.774, respectively. AUC of combined detection was 0.882, greater than those of single index (Z = 4.742, P = 0.000; Z = 4.346, P = 0.000; Z = 4.360, P = 0.000; Z = 3.726, P = 0.000; Z = 2.776, P = 0.006). Conclusions aEEG score combined with HRV parameters have high predictive efficiency for early prognosis in acute ischemic stroke patients after mechanical thrombectomy, which can assist clinical determination.